Strategi Pengembangan Agrowisata Lebah Etno Bali di Desa Baha Kecamatan Mengwi Kabupaten Badung Provinsi Bali (Jurnal Agribisnis dan Agrowisata, 2026)
Strategy for the Development of Balinese Etno Bee Agrotourism in Baha Village, Mengwi District, Badung Regency, Bali Province. Lebah Etno Bali Agrotourism offers tourism activities related honey bee farm. As a new agritourism attraction, there are many potentials of tourism attraction can be created and optimized. Therefore Lebah Etno Bali Agrotourism needs some strategies to expand market share and develop agrotourism based business models. The study aimed to identify internal and external factors that influence the development of agrotourism and to formulate a strategy for the development of Lebah Etno Bali Agrotourism. This study uses a qualitative descriptive analysis method which includes interviews and observations as well as quantitative data which includes the IFAS, EFAS, IE, and SWOT matrices. The results showed that the I-E matrix analysis was in cell V, this position indicated that Lebah Etno Bali Agrotourism was in a position to hold and maintain. In this position, the strategies commonly used are market penetration strategies and product development strategies. The SWOT analysis resulted in four alternative strategies, namely: (a) Strength-Opportunity Strategy (expanding the market by highlighting tourist attractions and product excellence, and establish cooperation with the government, entrepreneurs, and travel agents in the development of agrotourism), (b) Strength-Threat Strategy (improve accessibility to support the convenience of tourists when visiting Lebah Etno Bali Agrotourism, and product diversification to attract tourists), (c) Weakness-Opportunity Strategy (improve agrotourism support facilities to support the convenience of tourists optimizing promotional activities on Lebah Etno Bali Agrotourism to reach a wider market share), (d) Weakness-Threats Strategy (conduct training for agrotourism employees to improve the quality of human resources developing tourist attractions based on environmental sustainability to attract tourists).
Keywords: agrotourism; honey bees; strategy; SWOT